The manifestation of love in Hakim NezariQahestani”™s poetry - Jalili, Hamide; Mashhoor, Parvindokht (Revista Publicando, 2018)
In Persian poetry, the widest spiritual and emotional horizons are the horizons of ghana poetry. Persian Ghazal poetry is one of the richest forms of poetry, and a perfect example in which all the concepts of poetry can be seen in it well. Since the main form of Nezari”™s poetry isghanaieghazal and love is the main subject of ghanaei poetry and the essence of Persian poetry, this article is about how to manifest love as the most frequent type of GhanaeiinNezari”™s poetry under the titles: types of love, praise of love, description of beloved, traits of true lover, and effects of love (marriage, divorcing and divining), and the contrast between reason and love through a descriptive-analytical method.